Effect of amoebiasis on serum electrolytes in children diarrhea - Aljebory M. Abdul-Hussein (College of Pharmacy / Mustansiriyah University, 2006)
This study has been performed on 54 patients with Amoebiasis after they head diagnosed by microscopic examination and we have ignore other causes of diarrhea. The aim of this work is to study the effect of diarrhea caused by Amoebiasis in children on some of biochemical variables. The patients were divided into three groups according to the age, the control consist of 22 children with out Amoebiasis (healthy chilled) .The results of each age group of patients were compared with the same age group of the control, also the results indicated that the level of serum total, direct and indirect bilirubin in patients with Amoebiasis was significantly higher than that for control for each age group. The results indicated that the level of serum sodium, potassium, chloride, calcium and phosphorous of the patients was significantly lower than that for control in each age group. This study indicates that the diarrhea caused by Amoebiasis affected some of the liver and the intestine functions, which leaded to some biochemical changes in serum.